Some evidence on the relationship between social exclusion and high speed rail systems. Issue 1 (2nd January 2017) - Pagliara, Francesca; Biggiero, Luigi
ABSTRACT: Most of the impacts brought about by high-speed rail (HSR) systems have been widely examined in the literature. However, little attention has been paid to the question of social exclusion and economic investments in HSR systems. This paper aims to fill this gap by focusing on understanding the reasons why users feel they are socially excluded from these services. A revealed preference survey was carried out using the Google platform, interviewing users of the Italian transport network who were travelling for a variety of purposes, including road (car and bus), rail and HSR. Through the questionnaire, socio-economic data about the travellers have been collected, as well as information about the trip, i.e. its purpose, the transport mode chosen, and the origin and destination. However, in order to understand what prevents travellers from using HSR, factors other than cost have turned out to have an impact. Indeed, a mode choice model has been specified and calibrated, and the main outcome of the analysis is that geographical exclusion, i.e. low accessibility to the arrival/departure HSR station, is a relevant factor inhibiting users from choosing the service.